2012
DOI: 10.1038/nature10776
|View full text |Cite|
|
Sign up to set email alerts
|

Conditional modulation of spike-timing-dependent plasticity for olfactory learning

Abstract: Mushroom bodies are a well-known site for associative learning in insects. Yet the precise mechanisms that underlie plasticity there and ensure their specificity remain elusive. In locusts, the synapses between the intrinsic mushroom body neurons and their postsynaptic targets obey a Hebbian spike-timing-dependent plasticity (STDP) rule. Although this property homeostatically regulates the timing of mushroom body output, its potential role in associative learning is unknown. Here we show in vivo that pre-post … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
205
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(217 citation statements)
references
References 42 publications
10
205
0
2
Order By: Relevance
“…Without lateral inhibition in the output it is not possible to organize competition to have neurons responding for a particular set of stimulus [118,104]. In fact, it has been shown that there is strong lateral inhibition in the β -lobes in the MBs in [119] which is consistent with standing theoretical models [117,120,118,104,121].…”
Section: The Formation Of Memories In the Mushroom Bodiessupporting
confidence: 70%
See 1 more Smart Citation
“…Without lateral inhibition in the output it is not possible to organize competition to have neurons responding for a particular set of stimulus [118,104]. In fact, it has been shown that there is strong lateral inhibition in the β -lobes in the MBs in [119] which is consistent with standing theoretical models [117,120,118,104,121].…”
Section: The Formation Of Memories In the Mushroom Bodiessupporting
confidence: 70%
“…We hypothesized that mutual inhibition exists in the MB lobes and, in joint action with 'Hebbian' learning is able to organize a non-overlapping response of the decision neurons [104]. Recently this hypothesis was verified in [119] showing that the inhibition in the output neurons is fairly strong, and in [108] where plasticity was found from the KC neurons into the output ones.…”
Section: Learning Pattern Recognition In the Mushroom Bodiesmentioning
confidence: 87%
“…Responses in the central brain appear to follow these frequency-and modality-specific inputs, as has already been documented in larger insects, such as locusts and bees (Cassenaer and Laurent 2012; Denker et al 2010;Laurent and Naraghi 1994). In locusts, a 20-to 30-Hz oscillation initiated in feedback circuits of the antennal lobes is perpetuated by feedforward circuits to the mushroom bodies in the central brain (Cassenaer and Laurent 2012). Oscillatory activity in the mushroom bodies, in this olfactory-driven frequency domain, is then thought to be involved in tuning the precise timing of action potentials involved in synaptic plasticity mechanisms (Cassenaer and Laurent 2007).…”
Section: Discussionmentioning
confidence: 83%
“…In locusts, endogenous oscillations in olfactory neurons are involved in encoding odor cues (Cassenaer and Laurent 2012;Laurent and Naraghi 1994). In the fruit fly, Drosophila melanogaster, visual salience has been linked to increased 20-to 30-Hz activity in the brain (van Swinderen and Greenspan 2003), and these oscillations appear to have behavioral relevance for stimulus selection and suppression (Tang and Juusola 2010;van Swinderen 2007).…”
mentioning
confidence: 99%
“…postsynaptic forms, and (3) short-vs. long-term forms. In addition, these basic types of plasticity can be combined in various ways to make hybrids with different functional characteristics (Bailey et al 2000;Antonov et al 2003;Cassenaer and Laurent 2012;Huang et al 2012). For example, modulatory transmitters can act on presynaptic receptors to enhance short-term plasticity (such as post-tetanic potentiation [PTP]) of the evoked release of glutamate, leading to greater recruitment of postsynaptic mechanisms and greater long-term plasticity (Puzzo et al 2008).…”
mentioning
confidence: 99%